Evaluation of apparently healthy Egyptian infants and toddlers on the bayley-III scales according to age and sex - Zeinab M. Monir; Ebtissam M. Salah El-Din; Wafaa A. Kandeel; Sara F. Sallam; Eman Elsheikh; Mones M. Abushady; Fawzia Hasseb Allah; Sawsan Tawfik; Dina Abu Zeid (BMC, 2024)
Abstract Background Child development is shaped throughout the first years of life through the interaction of genetics and the environment. Bayley-III is valuably used to determine early developmental delay (DD). The aim of this study was to detect the differences in performance of a sample of apparently healthy Egyptian infants and toddlers on the Bayley-III scales in relation to their age and gender. Methods This was a cross-sectional study. Bayley scales were applied to 270 of the 300 recruited children following the inclusion criteria; to avoid potential risk factors affecting development. Assessment included cognitive, language and motor skills. Engaged children aged 18-42 months were divided into 4 age groups with six-month intervals. Results Approximately 78.4%, 76.2%, and 72% of the participants had average and above average scores in the cognitive, motor, and language domains, respectively. The language domain was characteristically impacted. The oldest age group (36-42 months) scored the highest means composite scores, while the 2nd group aged 24 - <30 months, scored the lowest means in the three evaluated domains. In general, girls had non-significantly higher composite scores than boys, with a small effect size (d = 0.2-0.4). In the language domain, girls aged 30 to < 36 months scored significantly higher composite scores than boys (p < 0.05), with a medium effect size (d = 0.73). Conclusion The study indicates that the performance of apparently healthy Egyptian children on the Bayley III evaluation differs in relation to age and sex. The most vulnerable age group at potential risk of DD was children aged 24-30 months. Efforts must be directed to investigate the nutritional, physical, psychological and safety needs of this group. Attention must be paid to early childhood intervention programs that stimulate development, especially language development, and they must be tailored on the basis of age and gender. Gender-specific norms may be needed in the evaluation of language development.